The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s1516-89132003000100004
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of wheat genotypes to soil aluminum differential saturations

Abstract: Ten wheat (Triticum aestivum) genotypes were evaluated in microplots with aluminum saturation of 0, 15, 30 and 45%, during 1994, in Londrina, Paraná, Brazil. The soil was a Distrofic Red Latosol (Typic Haplorthox), with 65% saturation of aluminum, amended with dolomitic lime. Variables evaluated included grain yield and yield components: ears.m-2, grains.ear-1 and the weight of 1000 grains. Genotypes differed in yield and yield components. Increasing aluminum saturation decreased yield, ears.m-2 and grains.ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 4 publications
1
4
0
1
Order By: Relevance
“…Benin et al (2004) evaluated oat genotypes and observed root growth retaking values that allowed a perfect discrimination between the sensitive and tolerant genotypes. Similar results were obtained by Freire et al (1987) in rice, by Baligar et al (1990) in sorghum and in wheat by Costa et al (2003). Cultivar Oeiras MG-6851presented a higher RL in the treatments with the presence of aluminum during the germination, regardless of aluminum absence or presence during the seedling growth.…”
Section: Resultssupporting
confidence: 88%
“…Benin et al (2004) evaluated oat genotypes and observed root growth retaking values that allowed a perfect discrimination between the sensitive and tolerant genotypes. Similar results were obtained by Freire et al (1987) in rice, by Baligar et al (1990) in sorghum and in wheat by Costa et al (2003). Cultivar Oeiras MG-6851presented a higher RL in the treatments with the presence of aluminum during the germination, regardless of aluminum absence or presence during the seedling growth.…”
Section: Resultssupporting
confidence: 88%
“…The crops growth in acid soil is generally poor due to saturation of Al in the soil (the degree of Al saturation is defined as the percentage of exchangeable Al relative to the total exchangeable cations) [9][10][11][12]. In a strongly acid soil (pH < 5.0), Al toxicity is considered as the greatest damaging factor for crops [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Al toxicity has been recognized, for a long time, as the main limiting factor of the plant growth in the acidic soils (Hartwell and Pember, 1918;Magistad, 1925). Al reduces the plant development as a whole (Randall and Vose, 1963;Costa et al, 2003) and interferes with the root elongation (Matsumoto and Morimura, 1980), nutrients' uptake, transport and use (e.g. phosphorus -P) (McCormick and Borden, 1972;Adrew and Berg, 1973;McCormick, 1974;Fleming, 1983).…”
Section: Introductionmentioning
confidence: 99%